The Relationship of Mental Health, Mindfulness, and Resilience with the Prevalence of Depression in Diabetic Patients in Rasht City - Moradmard Sougah, Mojgan; Majidi, Seyed Ali (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to examine the relationship between mental health, mindfulness, and resilience with depression among diabetic patients in Rasht city.Methods and Materials: This applied study employed a descriptive correlational design. The statistical population consisted of all diabetic patients aged 30 to 60 years who were referred to hospitals in Rasht city in 2025, totaling 476 individuals. Using Cochran’s finite population formula and convenience sampling, 316 participants were selected. Data were collected using the Beck Depression Inventory (Beck et al., 1996), the Mental Health Questionnaire (Besharat, 2009), the Connor–Davidson Resilience Scale (Connor & Davidson, 2003), and the Five Facet Mindfulness Questionnaire (Baer et al., 2006). Data were analyzed using SPSS version 24. Descriptive statistics were used to summarize the data, and inferential statistics, including Pearson correlation and multiple regression analysis, were employed to examine the relationships and predictive roles of mental health, mindfulness, and resilience in depression.Findings: The results of multiple regression analysis indicated that mental health had a significant negative relationship with depression, F(2, 313) = 17.36, p = 0.002, explaining 13.7% of the variance in depression. Mindfulness also demonstrated a significant negative relationship with depression, F(5, 310) = 14.36, p = 0.001, accounting for 21.4% of the variance. Furthermore, resilience showed a significant negative relationship with depression, F(4, 311) = 15.63, p = 0.001, explaining 34.8% of the variance in depression. Regression coefficients indicated that psychological well-being, mindfulness components, and resilience components were all significant negative predictors of depression (p < 0.01), with resilience demonstrating the strongest predictive effect.Conclusion: The findings indicate that mental health, mindfulness, and resilience are significant protective psychological factors associated with reduced depression among diabetic patients, highlighting the importance of strengthening these psychological resources in order to improve mental health and reduce depressive symptoms in this population.